Earlier leaf‐out rather than difference in freezing resistance puts juvenile trees at greater risk of damage than adult trees. (10th April 2014) - Vitasse, Yann; Lenz, Armando; Hoch, Günter; Körner, Christian; Piper, Frida
Summary In temperate climates, seedlings and saplings have often been assumed to be more sensitive to late‐spring freezes than conspecific adult trees. Yet, no data are available to compare the freezing resistance of juvenile and adult trees at their phenologically most sensitive stage, that is, during leaf‐out. Emerging leaves of seedlings, saplings and adult trees were collected in spring 2013 in seven temperate tree species in a mature mixed forest in the foothills of the Swiss Jura Mountains. Freezing resistance of these emerging leaves was assessed using different target temperatures (−13 to +4 °C) in seven computer‐controlled freezers. Additionally, we assessed the risk that species encounter freeze damages based on temperature data recorded since 1898. The different study species showed contrasting freezing resistance, with the LT50 (median lethal freezing temperature) of emerging leaves ranging from −3.5 ± 0.2 °C (Fraxinus excelsior) to −8.3 ± 0.2 °C (Prunus avium). Within species, juvenile trees (seedlings or saplings) were found to be as sensitive to freezing temperatures as mature trees when the same developmental stage of foliage was compared. Based on phenological observations made during spring 2012, long time series of temperatures indicate a very low risk of freeze damage at the study site, especially for adult trees. Synthesis. We conclude that seedlings and saplings are more prone to freeze damage than adult trees because of their earlier flushing rather than due to a higher sensitivity to freezing as such. Our study highlights that the timing of spring phenology has evolved in such a way that it minimizes the risk of freeze damage according to the species‐specific LT50. Early flushing species are among the most freezing‐resistant species during flushing, whereas late flushing species are among the least resistant. We conclude that for the examined species the species‐specific freezing resistance during leaf emergence could be extracted from either adult or juvenile trees, as long as it is estimated at a same phenological stage.